2010
DOI: 10.1521/aeap.2010.22.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Taking it to the Pews: A CBPR-Guided HIV Awareness and Screening Project with Black Churches

Abstract: Utilizing a community-based participatory research (CBPR) approach is a potentially effective strategy for exploring the development, implementation, and evaluation of HIV interventions in African American churches. This CBPR-guided study describes a church-based HIV awareness and screening intervention (Taking It to the Pews [TIPS]) that fully involved African American church leaders in all phases of the research project. Findings from the implementation and evaluation phases indicated that church leaders del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 28 publications
2
122
0
Order By: Relevance
“…Their preference was to collaborate with other organizations that conducted condom education or targeted gay/bisexual men -but not in the church. Finally, although a TIPS case study found that increased exposure to TIPS tools was related to lower HIV stigma and increased HIV testing intentions, 12 future tool kit research using community trials is needed. To this end, we are pilot testing a TIPS HIV Tool Kit intervention versus a standard HIV information intervention on HIV testing rates with church members and community members who use church services.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Their preference was to collaborate with other organizations that conducted condom education or targeted gay/bisexual men -but not in the church. Finally, although a TIPS case study found that increased exposure to TIPS tools was related to lower HIV stigma and increased HIV testing intentions, 12 future tool kit research using community trials is needed. To this end, we are pilot testing a TIPS HIV Tool Kit intervention versus a standard HIV information intervention on HIV testing rates with church members and community members who use church services.…”
Section: Discussionmentioning
confidence: 98%
“…Our preliminary focus groups and ongoing discussions with church leaders further indicated the need to increase HIV education among church leaders, which is reported elsewhere. 12 In addition, a promising number of churches had facilitated HIV screening events. To increase communitywide church capacity to address HIV education and screening, the development of the TIPS Project and its tools included creating several routinized strategies to train church leaders on HIV topics and the HIV Tool Kit, and to simplify the process for their churches to facilitate HIV screening events.…”
Section: Community-level Approachesmentioning
confidence: 99%
See 3 more Smart Citations